The Virtual Reality Socialization and Training: Virtual Tour - Firmansyah, Hasbi; Budiraharjo, Eko; Sofyan, Ali (ASEAN Journal of Empowering Community, 2022)
The rapid world of virtual reality (VR) technology provides opportunities for school promotion media using VR widely, namely Virtual Tour training. FIRST This also challenges SMK MUTU to understand better the effectiveness of VR experiences in encouraging better attitudes towards promotional objectives and shaping visiting patterns. SECOND: This basic procedure is technical for taking panoramic images, identifying the resulting panoramic images owned, and observing 360-degree changes when processed in 3DVISTA software. THIRD If the panoramic image has become 360o, then make it into a series of images so that when processed, it will become a single image that is more alive in 3D like Google Street View, when in compile Virtual Tour will provide an experience where users can interact with a 3D image. FOURTH how positive are the consequences of the feeling of presence in the VR experience for the first time, the feeling of being in a virtual environment increases the peak of enjoyment of VR users both the increased touch of VR technology, such as being there results in a stronger sense of liking and preference at the destination. A positive attitude change leads to a higher level of intention to visit.